2022
DOI: 10.3390/life12070976
|View full text |Cite
|
Sign up to set email alerts
|

Trifid Mandibular Condyle: Case Report and Current Review of the Literature

Abstract: Trifid mandibular condyle (TMC) is a rare anatomical variation characterized by the duplication of the mandibular condyle. The aim of this study is to report a new case of a 26-year-old female patient with a left TMC and to review the current existing literature on TMC, the relevant cases, etiology, symptoms and different treatment modalities. The database engines PubMed, EMBASE, Scopus, Web of science, Scientific Electronic Library Online, Cochrane and CINAHL were searched for TMC cases from inception until A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The metaplasia of local fibroblasts in the condylar neck produces a new condylar head at the normal anatomical site, while the original displaced condylar head undergoes resorption. As a result, the traumatized joint will have two or more condyles [ 5 ]. This is in concordance with our explanation regarding the formation of three coronoid processes following an episode of trauma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The metaplasia of local fibroblasts in the condylar neck produces a new condylar head at the normal anatomical site, while the original displaced condylar head undergoes resorption. As a result, the traumatized joint will have two or more condyles [ 5 ]. This is in concordance with our explanation regarding the formation of three coronoid processes following an episode of trauma.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the literature has been focused on reporting anomalies of the condylar process such as “bifid condyle,” “trifid condyle,” and “tetrafid condyle” [ 4 ]. The reporting of these variations of the mandibular condyle has increased with the advent of advanced imaging techniques, especially computed tomography (CT), cone beam computed tomography (CBCT), and magnetic resonance imaging (MRI) [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although many literatures state that BMC is an asymptomatic, it has been reported that patients with BMC experience difficulty in occlusion and mastication. 5,9 Changes that occur in the head of the condyle cause deformity in the articular fossa fossa. This causes disruption of the function of speech, mastication and limited mouth opening.…”
Section: Discussionmentioning
confidence: 99%
“…This case can appear unilaterally or bilaterally without any differences in sex or racial preferences. 3,4,5,6 Bifid Mandibular Condyle (BMC), also known as a double-headed condyle is a condition of bone disorder in which the articular surface of the condyle is divided into two parts; anterioposterior and mediolateral. 8 The condylar division ranges from a superficial groove to two different condyles with separate necks.…”
mentioning
confidence: 99%